Cross-sections for the H+H2O -> OH+H-2 and H+D2O -> OD+HD abstraction reactions - Brouard, M; Marinakis, S; Lago, L; Quadrini, F; Solaiman, D; Vallance, C; Aoiz, F; Banares, L; Castillo, J (2004)
Absolute values of the cross-section for the abstraction reaction between fast H atoms and D2O have been determined experimentally at mean collision energies of 1.83 eV and 2.48 eV. The data support the value for the cross-section recently reported for the H + H2O reaction at 2.46 eV, which was significantly lower than previous measurements. The measurements employ the photodissociation of water as a calibrant for OH(OD) concentration. The OH rotational quantum state population distributions for the fully protonated reaction, as well as those for the photodissociation of water, are shown to be in good agreement with previous work. The measurements are compared with new quasi-classical trajectory calculations and published quantum mechanical scattering calculations using the most recently developed potential energy surface.